Validity of Immunoglobulin M Anti Salmonella typhi Serologic Test in Childhood Typhoid Fever - Hilda Marsela; Djatnika Setiabudi; Agnes Rengga Indrati (Althea Medical Journal, 2017)
Background: Typhoid fever, which mostly affects children, remains a major health problem in developing countries. Early diagnosis will help the management and thus, reduce morbidity and mortality. However, a rapid diagnostic test that detects the presence of immunoglobulin M (IgM) directed towards Salmonella typhi (S. typhi) antigen remains controversial despite its popularity. This study was aimed to assess the validity of IgM anti S. typhi serologic test in childhood typhoid fever. Methods: This retrospective diagnostic test, used blood culture as gold standard. Forty-one typhoid fever children with fever of 1–14 days admitted to Dr. Hasan Sadikin General Hospital Bandung from 2013 to 2015 were recruited. Diagnosis of typhoid fever is made clinically. Data were analyzed by Receiver Operating Characteristic (ROC) curve and diagnostic test.Results: Forty one children diagnosed with typhoid fever, 37 were positive for IgM anti S. typhi, but only 18 were positive for S. typhi in blood culture. IgM anti S. typhi (cut-off ≥4) test had an Area Under the Curve (AUC) of 59%, sensitivity of 100% and specificity of 17.39%. IgM anti S. typhi with cut-off >8 showed the highest AUC with sensitivity of 55.56% and specificity of 73.68%.Conclusions: IgM anti S. typhi test of cut-off >8 performs better than cut-off ≥4 in terms of AUC..[AMJ.2017;4(1):138–42] DOI: 10.15850/amj.v4n1.1035